Supervising student teachers - Ediger, Marlow
Each student teacher must provide the best in objectives, learning activities, and evaluation procedures in any given teaching situation. The supervisor needs to guide the professional to achieve optimally in student teaching and thus develop into a truly professional teacher.
Keywords: Student teachers -- Supervision of; Student teachers -- Rating of; Student teachers -- Training of; Student teaching